1975
DOI: 10.1002/j.1552-4604.1975.tb01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen and Aspirin in Rheumatoid Arthritis: A Multicenter Double‐Blind Crossover Comparison Study

Abstract: One hundred nineteen adults with active definite or classical rheumatoid arthritis were studied in a multicenter double-blind crossover study of naproxen (500 mg/day) and aspirin (3.6 Gm/day). Each drug was given in sequence for a six-week study period. Patients already receiving corticosteriod and/or gold therapy were maintained at constant dose throughout the study, but analgesics and other nonsteroidal antiinflammatory agents were discontinued at baseline. Objective and subjective evaluations by both invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Comparative studies showed that there are no significant differences as regards the therapeutic efficacy of the studied compounds, but NX is better tolerated than aspirin [2]. The concomitant administration of NX with aspirin was shown to be more effective than of aspirin alone [3].…”
Section: Introductionmentioning
confidence: 98%
“…Comparative studies showed that there are no significant differences as regards the therapeutic efficacy of the studied compounds, but NX is better tolerated than aspirin [2]. The concomitant administration of NX with aspirin was shown to be more effective than of aspirin alone [3].…”
Section: Introductionmentioning
confidence: 98%
“…3.1 6 The drug was shown to be a potent anti-inflammatory agent in standard animal assays, with activity greater than aspirin, phenylbutazone, mefenamic acid and hydrocortisone, but somewhat less than indomethacin.' 6 , 2 8 In analgesic studies the drug was more potent than aspirin and phenylbutazone, but had only 10% of the activity of indomethacin.…”
Section: Introductionmentioning
confidence: 99%
“…In 100 postoperative patients, Stetson and associates 17 found that 400 mg of naproxen is more effective than 25 mg of meperidine; in 105 orthopedic patients, Ruedy and MeCuIIough 14 found that 600 mg of naproxen is more effective than 65 mg of propoxyphene, Ruedy13 also found that 400 mg of naproxen was more effective than 325 mg of aspirin plus 30 mg of codeine in 63 dentaloutpatients . In 4 studies on the treatment of chronic rheumatoid arthritis (studies ranging from 4 wk duration to 2 yr), naproxen 250 mg two times daily was more effective than placebo in 38 patients 10,11 and as effective as aspirin, 3.6 gm daily, in 119 patients 5 for the relief of symptoms. In a group of 28 patients using cortisone to control the symptoms of rheumatoid arthritis, Flores and Rojas 6 reported a marked reduetion in need for cortisone with 400 mg naproxen daily.…”
mentioning
confidence: 99%